THE TRADITIONAL MUSIC SAPE' THERAPY ON POST OPERATING PAIN SCALE REDUCTION AT SANTO VINCENTIUS HOSPITAL SINGKAWANG CITY - Ndeta, Egidius Umbu (Tanjungpura Journal of Nursing Practice and Education, 2020)
Background : The severity of postoperative pain depends on the individual's physiological and psychological assumptions, the established tolerance for pain, the location of the incision, the nature of the procedure, the depth of surgical trauma and the type of anesthetic agent and how the agent is administered. Apart from pharmacological action, pain can also be treated with music. Music is an expression of one's soul and one's communication language. Music can sometimes make people cry, laugh, even music can heal sick people. Sape 'or also known as sampe is a musical instrument or instrument originating from the Dayak Kenyah and Kayan tribes. This traditional musical instrument is starting to become worldwide and favored by the international community, the sound of the sape 'is soft and easy to animate.Research Purposes : The effect of traditional music SAPE' therapy on postoperative pain reduction at Santo Vincentius Hospital  Singkawang city.Research Methods : Experimental research with pre and post test control group design. The sample selection used consecutive sampling method. The number of samples was 14 respondents after laparotomy surgery (7 samples from the intervention group and 7 samples from the control group). Data analyzed by using Paired Sample t Test.Result : Respondents were female, namely as many as 85.7%, aged 26-35 years, namely as many as 50.3% and had no experience of surgery, namely as many as 35.7%. The mean score for the pre intervention group was 7.29, while the average for the post intervention group was 5.29. The average of the music therapy intervention group with sape 'was 2,000, while the mean for the control group was 0.429. The average difference between the two groups was 1,571. The  statistic results of Paired Sample t Test with  p 2-tailed was significant of 0.002.Conclusion : There is an effect of traditional sape music therapy on reducing the pain scale of post surgery at RSU Santo Vincentius Singkawang.